Factors Associated with Adherence to Diabetic Retinopathy Screening Among Patients Attending a Nurse-Led Community Clinic in Australia: A Qualitative Study - Fouziah Almouqati; Judith Daire; Catherine Catanach; Jean-Louis deSousa; Sam Quill; Mohamed Estai (Nursing Reports)
Background/Objectives: Despite the availability of screening services, the rate of diabetic retinopathy (DR) screening continues to be suboptimal in Australia, necessitating improvement. However, improving DR screening rates requires a more comprehensive understanding of the factors influencing adherence to the screening recommendations. This study aimed to explore the factors that influence adherence to DR screening among people with diabetes attending a community screening clinic in Australia. Methods: This qualitative study included purposively patients with diabetes recruited from a nurse-led community screening clinic in Australia. Semi-structured interviews were conducted to explore barriers and enablers impacting patient adherence to DR screening recommendations. The interview data were analyzed thematically using NVivo based on the socio-ecological model, with salience identified by the frequency of the theme. Results: A total of 22 participants completed the interview, including 10 females with a mean age of 60 ± 16.2 years. The interviews identified several factors that improved adherence to DR screening guidelines, including (a) knowledge of the connection between DR and diabetes and the importance of the screening, (b) the care provider’s recommendations, and (c) pre-booked appointments and automatic invitations. Beyond these factors, clinic staff interactions, family support, fear of vision loss, flexible clinic hours, and transportation accessibility also facilitate DR screening adherence. Conclusions: The present study identified key multi-level factors influencing adherence to DR screening. While these findings from a single clinic provide valuable insights to inform screening strategies, larger multi-center studies are needed to validate their broader applicability across diverse healthcare settings and populations.